2016
DOI: 10.1186/s12889-016-3432-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of dengue fever in Nepal from 2010 to 2014

Abstract: BackgroundDue to recent emergence, dengue is becoming one of the major public health problems in Nepal. The numbers of reported dengue cases in general and the area with reported dengue cases are both continuously increasing in recent years. However, spatiotemporal patterns and clusters of dengue have not been investigated yet. This study aims to fill this gap by analyzing spatiotemporal patterns based on monthly surveillance data aggregated at district.MethodsDengue cases from 2010 to 2014 at district level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…The clustering of incidence of DF in Makassar city has a tendency to follow by high population densities, the economic conditions of the community, especially nutrition, and the geographical conditions such as urban and rural areas. These results were confirmed by studies carried out by Honorato et al [7], Acharya et al [8], Thamrin and Taufik [12] and Hu et al [13]. The number of larvae is also likely to affect the spread of DF but has not been included as a contributing factor in this paper [5].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The clustering of incidence of DF in Makassar city has a tendency to follow by high population densities, the economic conditions of the community, especially nutrition, and the geographical conditions such as urban and rural areas. These results were confirmed by studies carried out by Honorato et al [7], Acharya et al [8], Thamrin and Taufik [12] and Hu et al [13]. The number of larvae is also likely to affect the spread of DF but has not been included as a contributing factor in this paper [5].…”
Section: Resultssupporting
confidence: 82%
“…The spatial distribution of dengue incidence in Brazil in 2010 using the model Bayesian was discussed by Honorato et al [7]. Temporal spatial analysis of DFhas been done by Acharya et al [8], Ling et al [9] and Huang et al [10]. Geographical inequality in DF considering Bayesian approach using spatial random effects and geographical mapping of DF were done by Thamrin and Taufik [11] and Thamrin and Alimun [12], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the population growth, human migrations, urbanization, and spread of mosquitoes, dengue incidence has increased dramatically in many provinces in mainland China, with several big outbreaks occurring in Guangzhou and Yunnan Provinces (Sang et al, 2015;Sun et al, 2017;Lai et al, 2015). Amid the great challenge from re-occurrence of infectious disease, spatial statistics analysis techniques were widely used to explore the temporal and spatial distribution characteristics of dengue and other infectious diseases (Atique et al, 2018;Desjardins et al, 2018;Acharya et al, 2016;Ling et al, 2014;Yanez-Arenas et al, 2018). For example, Suleman et al identified spatio-temporal clusters with dengue outbreak in Swat, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…The spatiotemporal analysis (2010-2014) has shown that Chitawan District (home for first case of DF) is the hotspot of DF followed by Jhapa and Parsa Districts [99]. Now, Dengue virus is spread even in hilly areas including Kathmandu Valley [99]. This has been thought to be associated with change in climate and biodiversity [3,[100][101][102].…”
Section: Emerging Infectionsmentioning
confidence: 99%
“…Scrub typhus: Though, serological evidence of existence of scrub typhus in eastern Nepal was reported long back in 1981 clinical cases reported in 2015 with high numbers from Chitawan District where in 2004, also the first case of Fig. 8 Annualized average incidence of dengue fever in Nepal (2010Nepal ( -2014 [99] dengue fever was recorded [94,114,115]. In the year 2016, over 800 cases were detected from all over the country out of which 14 (1.7%) died.…”
Section: Emerging Infectionsmentioning
confidence: 99%